Pre-lithiated negative pole piece, preparation method of lithium supplementing composite layer, lithium supplementing method, secondary battery and electronic device

By using prelithiation technology in the negative electrode sheet of lithium-ion battery, and using lithium foil or lithium alloy foil and interface particles to form a lithium-complement composite layer, the problems of low efficiency and poor cycle life of the negative electrode sheet of lithium-ion battery are solved for the first time, and a higher energy density is achieved.

CN119920904AActive Publication Date: 2025-05-02NINGDE AMPEREX TECHNOLOGY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510111680.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The first time the Coulombic efficiency and poor cycle life of the existing lithium-ion battery negative electrode sheets are low, which cannot meet the needs of increasing energy density.

Method used

The lithium content and lithium supplement uniformity of the negative electrode material are improved by using lithium foil or lithium alloy foil in the lithium supplement composite layer.

Benefits of technology

It improves the first Coulomb efficiency of lithium-ion batteries, reduces the cycle capacity attenuation, and increases the battery's energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920904A_ABST
    Figure CN119920904A_ABST
Patent Text Reader

Abstract

The invention provides a pre-lithiated negative electrode plate, which comprises a negative electrode material layer, and the negative electrode material layer comprises a first surface and a second surface which are opposite to each other. From the first surface to the second surface, the negative electrode material layer sequentially comprises a first region, a second region and a third region, and the third region is located on the surface of the negative electrode current collector. The thickness of the first region accounts for 1 / 3 of the thickness of the negative electrode material layer, the thickness of the second region accounts for 1 / 3 of the thickness of the negative electrode material layer, and the thickness of the third region accounts for 1 / 3 of the thickness of the negative electrode material layer. Based on the mass of the first region, the mass percentage content of the lithium element is W1, based on the mass of the second region, the mass percentage content of the lithium element is W2, based on the mass of the third region, the mass percentage content of the lithium element is W3, W1 > W2 > W3, W1 / W2 is larger than or equal to 1.01 and smaller than or equal to 2.0, and W2 / W3 is larger than or equal to 1.01 and smaller than or equal to 2.0. The pre-lithiated negative pole piece meets the characteristics, the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation is reduced, and the energy density of the secondary battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a pre-lithiated negative electrode plate, a preparation method of a lithium replenishing composite layer, a lithium replenishing method, a secondary battery and an electronic device. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high power, and long cycle life. They are widely used in consumer electronics, electric bicycles, and electric vehicles. As their application scope continues to expand, the energy density and cycle performance requirements of lithium-ion batteries continue to increase. The current common lithium-ion battery negative electrode graphite materials can no longer meet the requirements for energy density. Although silicon-carbon and silicon-oxygen negative electrode materials have high theoretical specific capacity, they are ideal materials to replace negative electrode graphite materials and improve the energy density of lithium-ion batteries. However, they have not been widely used due to their low first coulomb efficiency and poor cycle life. The existing method to improve the first coulomb efficiency and reduce cycle attenuation of silicon-carbon or silicon-oxygen negative electrodes is to pre-replenish lithium to the negative electrode plate to supplement the irreversible capacity consumed in the first charge, discharge, and cycle, improve the first coulomb efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrodes, and then improve the energy density of lithium-ion batteries.

[0003] The existing negative electrode plate lithium replenishment methods mainly include lithium powder replenishment, lithium strip replenishment and electrochemical replenishment. However, the above three lithium replenishment methods have certain problems in environmental control, lithium replenishment uniformity, and side reactions after lithium replenishment. Therefore, it is urgent to provide a pre-lithiated negative electrode plate that can improve the first coulomb efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrodes, reduce cycle capacity attenuation, and improve the energy density of lithium-ion batteries. Summary of the invention

[0004] The purpose of this application is to provide a pre-lithiated negative electrode plate, a preparation method of a lithium replenishing composite layer, a lithium replenishing method, a secondary battery and an electronic device to improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. The specific technical solution is as follows:

[0005] The first aspect of the present application provides a method for preparing a lithium supplement composite layer, which comprises the following steps:

[0006] (1) coating a lithium metal powder slurry on a support layer, drying it, and rolling it to form a lithium supplement layer; or rolling a lithium foil and / or a lithium alloy foil onto a support layer to form a lithium supplement layer; or coating a lithium or lithium alloy molten slurry on a support layer, cooling it, and rolling it to form a lithium supplement layer; wherein the rolling pressure P1 is 0.1T / 10mm to 2T / 10mm;

[0007] (2) coating the interface particles on the surface of the lithium replenishing layer to form an interface layer, and then rolling the layer, wherein the rolling pressure P2 is 0.1T / 10mm to 2T / 10mm, the rolling temperature T1 is 25°C to 170°C, and the rolling standing time t1 is 5min to 50min, to form a lithium replenishing composite layer.

[0008] In one embodiment of the present application, the lithium supplement composite layer includes a support layer, a lithium supplement layer and an interface layer, the lithium supplement layer is arranged between the support layer and the interface layer, the interface layer includes interface particles, and the lithium supplement layer includes at least one of lithium foil or lithium alloy foil.

[0009] The above method is used to prepare a lithium-replenishing composite layer, and then the negative electrode plate is pre-lithiated, which is beneficial to replenishing lithium for the negative electrode plate. The obtained pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0010] In one embodiment of the present application, the interface particles include at least one of a conductive agent or a lithium-intercalating material; the conductive agent includes at least one of conductive carbon black, carbon fiber, graphene or carbon nanotubes; the lithium-intercalating material includes at least one of artificial graphite, natural graphite, hard carbon, silicon-carbon material or silicon-oxygen material. By selecting the above-mentioned interface particles, the interface layer can have better electron and ion conductivity. During the pre-lithiation process, it is beneficial for electrons and lithium ions to be transferred to the surface or interior of the negative electrode material layer through the interface layer more quickly, which is beneficial for further replenishing lithium to the negative electrode plate, and can further improve the initial coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0011] In one embodiment of the present application, the thickness H1 of the interface layer is 0.1 μm to 50 μm, and preferably, the thickness H1 of the interface layer is 1 μm to 20 μm. The lithium atoms in the lithium replenishment layer lose electrons to form lithium ions, and the electrons and lithium ions are transferred to the surface or the inside of the negative electrode material layer through the interface layer. By regulating the thickness of the interface layer within the scope of the present application, the interface layer has a suitable thickness, the transmission distance of electrons and lithium ions is moderate, and the electrons and lithium ions can be effectively compounded to form lithium-inserted compounds, which is beneficial to further replenish lithium to the negative electrode plate, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0012] In one embodiment of the present application, the coverage ratio s1 of the interface particles in the lithium replenishing layer is 50% to 100%, preferably, the coverage ratio s1 of the interface particles in the lithium replenishing layer is 80% to 100%. The coverage ratio of the interface particles in the lithium replenishing layer is within the scope of the present application, the coverage ratio of the interface particles in the lithium replenishing layer is high, the uniformity of lithium replenishment in the negative electrode material layer is high, and the first coulomb efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the energy density of the secondary battery can be further improved.

[0013] In one embodiment of the present application, the interface particles are embedded in the lithium replenishing layer, and the depth of the interface particles embedded in the lithium replenishing layer accounts for 10% to 95% of the thickness of the interface layer. Preferably, the depth of the interface particles embedded in the lithium replenishing layer accounts for 20% to 70% of the thickness of the interface layer. When the interface particles are embedded in the lithium replenishing layer and the depth of the interface particles embedded in the lithium replenishing layer accounts for the thickness of the interface layer within the scope of the present application, the lithium inside the lithium replenishing layer can be better promoted to participate in the oxidation reaction, thereby better transferring the lithium inside the lithium replenishing layer to the negative electrode material layer, which is beneficial to further replenishing the negative electrode plate, further improving the initial coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery; it is also beneficial to the repeated use of the lithium replenishing composite layer.

[0014] In one embodiment of the present application, the support layer includes at least one of metal foil, polyethylene terephthalate film, polypropylene film or polyethylene film, and the metal foil includes copper foil, nickel foil, steel foil or copper-nickel alloy foil. By selecting the above support layer, the support layer can provide better support for the lithium replenishment layer and the interface layer, improve the mechanical strength of the lithium replenishment composite layer, so that the lithium replenishment composite layer can be peeled off from the surface of the negative electrode material layer more smoothly after lithium replenishment, reduce the possibility of fracture of the lithium replenishment composite layer, and be beneficial to the lithium replenishment of the negative electrode plate, so as to further improve the initial coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0015] The second aspect of the present application provides a lithium supplementation method, which comprises the following steps:

[0016] Drying a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector;

[0017] Any of the above-mentioned lithium-replenishing composite layers and the negative electrode plate are laminated so that the interface layer contacts the negative electrode material layer, and a pre-lithiation treatment is performed. The interface pressure P3 between the interface layer and the negative electrode material layer is 0.1 MPa to 2 MPa, the lamination time t2 between the interface layer and the negative electrode material layer is 0.5 h to 72 h, and the lamination temperature T2 between the interface layer and the negative electrode material layer is 50°C to 180°C. After the pre-lithiation treatment is completed, the lithium-replenishing composite layer and the negative electrode plate are peeled off to form a pre-lithiation negative electrode plate.

[0018] The lithium-replenishing composite layer is prepared by the preparation method of the lithium-replenishing composite layer provided in the present application, and then the pre-lithiated negative electrode plate is prepared by the lithium-replenishing method provided in the present application, which is beneficial to replenishing lithium for the negative electrode plate. The obtained pre-lithiated negative electrode plate is applied to the secondary battery, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0019] The third aspect of the present application provides a pre-lithiated negative electrode sheet prepared according to any of the aforementioned lithium supplementation methods, the negative electrode sheet comprising a negative current collector and a negative electrode material layer, and along the thickness direction of the negative electrode sheet, the negative electrode material layer comprises a first surface and a second surface relative to each other. From the first surface to the second surface, the negative electrode material layer comprises a first region, a second region and a third region in sequence, and the third region is located on the surface of the negative current collector. The thickness of the first region accounts for 1 / 3 of the thickness of the negative electrode material layer, the thickness of the second region accounts for 1 / 3 of the thickness of the negative electrode material layer, and the thickness of the third region accounts for 1 / 3 of the thickness of the negative electrode material layer. Based on the mass of the first region, the mass percentage of lithium element is W1, based on the mass of the second region, the mass percentage of lithium element is W2, based on the mass of the third region, the mass percentage of lithium element is W3, W1>W2>W3, 1.01≤W1 / W2≤2.0, 1.01≤W2 / W3≤2.0. Applying the above-mentioned pre-lithiated negative electrode plate to a secondary battery can improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity decay, and improve the energy density of the secondary battery.

[0020] In one embodiment of the present application, the negative electrode material layer includes a negative electrode active material, the negative electrode active material includes at least one of a carbon material or a silicon-containing material, the carbon material includes at least one of a graphite material or a hard carbon, and the silicon-containing material includes at least one of a silicon-carbon material or a silicon-oxygen material. The negative electrode material layer includes a negative electrode active material, the negative electrode active material includes the above substances, the pre-lithiated negative electrode plate has a higher lithium supplement amount, and the prepared secondary battery has a higher first coulomb efficiency, a lower cycle capacity attenuation, and a higher energy density.

[0021] In one embodiment of the present application, the negative electrode active material only includes silicon-containing substances. Based on the mass of the negative electrode material layer, the mass percentage of silicon in the negative electrode material layer is w1, 18.6%≤w1≤63.5%, 11.5%≤W1≤18.4%, 9.2%≤W2<11.5%, and 4.6%≤W3<9.2%. The negative electrode active material only includes silicon-containing substances, and the silicon-containing substances have a high gram capacity. The values ​​of the mass percentages of silicon w1, W1, W2, and W3 in the negative electrode material layer are within the scope of the present application. The negative electrode material layer has a high capacity, high ionic conductivity, and high electronic conductivity. The pre-lithiated negative electrode plate has a high lithium supplement amount. The above-mentioned pre-lithiated negative electrode plate is applied to a secondary battery, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0022] In one embodiment of the present application, the negative electrode active material includes a carbon material and a silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of silicon in the negative electrode material layer is w1, 1.1%≤w1≤3.4%, 0.38%≤W1≤0.60%, 0.30%≤W2<0.38%, 0.15%≤W3<0.30%. The negative electrode active material includes a carbon material and a silicon-containing substance. Within the same pre-lithiation treatment time, the lithium replenishment efficiency of different negative electrode active materials is different. The lithium replenishment amount of the silicon-containing substance is relatively small, and the lithium replenishment amount of the carbon material is relatively large, which will affect the lithium replenishment amount in the pre-lithiation negative electrode plate. The values ​​of the mass percentage w1, W1, W2, and W3 of the silicon element in the negative electrode material layer are within the scope of this application. The carbon material and the silicon-containing substance have a suitable mass percentage. The negative electrode active material has a higher capacity and a higher lithium replenishment amount, which can make the pre-lithiated negative electrode plate have a higher capacity and a higher lithium replenishment amount. Applying the above-mentioned pre-lithiated negative electrode plate to a secondary battery can further improve the first coulombic efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0023] In one embodiment of the present application, the negative electrode active material includes a carbon material and a silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of silicon in the negative electrode material layer is w1, 3.3%≤w1≤10.2%, 2.8%≤W1≤4.5%, 2.2%≤W2<2.8%, 1.1%≤W3<2.2%. The negative electrode active material includes a carbon material and a silicon-containing substance. Within the same pre-lithiation treatment time, the lithium replenishment efficiency of different negative electrode active materials is different. The lithium replenishment amount of the silicon-containing substance is relatively small, and the lithium replenishment amount of the carbon material is relatively large, which will affect the lithium replenishment amount in the pre-lithiation negative electrode plate. The values ​​of the mass percentage w1, W1, W2, and W3 of the silicon element in the negative electrode material layer are within the scope of this application. The carbon material and the silicon-containing substance have a suitable mass percentage. The negative electrode active material has a higher capacity and a higher lithium replenishment amount, which can make the pre-lithiated negative electrode plate have a higher capacity and a higher lithium replenishment amount. Applying the above-mentioned pre-lithiated negative electrode plate to a secondary battery can further improve the first coulombic efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0024] In one embodiment of the present application, the porosity of the first region is S1, the porosity of the second region is S2, and the porosity of the third region is S3, S1>S2>S3. S1, S2, and S3 satisfy the above-mentioned size relationship, which is conducive to the migration of lithium ions along the thickness direction of the negative electrode sheet and can improve the dynamic performance of the negative electrode sheet.

[0025] In one embodiment of the present application, 1.01≤S1 / S2≤1.5, 1.01≤S2 / S3≤1.5. The values ​​of S1 / S2 and S2 / S3 are within the scope of the present application, and the porosity of the first region is greater than the porosity of the second region and greater than the porosity of the third region, which is conducive to the migration of lithium ions along the thickness direction of the negative electrode sheet and can further improve the kinetic performance of the negative electrode sheet.

[0026] In one embodiment of the present application, the negative electrode active material includes only silicon-containing substances. Based on the mass of the negative electrode material layer, the mass percentage of silicon in the negative electrode material layer is w1, 18.6%≤w1≤63.5%, 42.1%≤S1≤57.0%, 38.0%≤S2<42.1%, 25.0%≤S3<38.0%. The negative electrode active material includes only silicon-containing substances, and the silicon-containing substances have a high gram capacity. The values ​​of the mass percentage of silicon w1, S1, S2, and S3 in the negative electrode material layer are within the scope of the present application, which is conducive to the migration of lithium ions along the thickness direction of the negative electrode plate, and can further improve the kinetic performance of the negative electrode plate. At the same time, the negative electrode plate has a high capacity.

[0027] In one embodiment of the present application, the negative electrode active material includes a carbon material and a silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of silicon in the negative electrode material layer is w1, 1.1%≤w1≤3.4%, 26.3%≤S1≤35.5%, 23.7%≤S2<26.3%, and 15.8%≤S3<23.7%. The negative electrode active material includes a carbon material and a silicon-containing substance, which is beneficial to further improve the gram capacity and lithium replenishment amount of the negative electrode active material. The mass percentage of silicon in the negative electrode material layer w1, S1, S2, and S3 is within the scope of the present application, which is beneficial to the migration of lithium ions along the thickness direction of the negative electrode sheet, and can further improve the kinetic performance of the negative electrode sheet. At the same time, the negative electrode sheet has a higher capacity.

[0028] In one embodiment of the present application, the negative electrode active material includes a carbon material and a silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of silicon in the negative electrode material layer is w1, 3.3%≤w1≤10.2%, 31.6%≤S1≤42.6%, 28.4%≤S2<31.6%, and 18.9%≤S3<28.4%. The negative electrode active material includes a carbon material and a silicon-containing substance, which is conducive to further improving the gram capacity and lithium replenishment of the negative electrode active material. The mass percentage of silicon in the negative electrode material layer w1, S1, S2, and S3 is within the scope of the present application, which is conducive to the migration of lithium ions along the thickness direction of the negative electrode sheet, and can further improve the kinetic performance of the negative electrode sheet. At the same time, the negative electrode sheet has a higher capacity.

[0029] The fourth aspect of the present application provides a secondary battery, which includes the pre-lithiated negative electrode plate in any of the above embodiments. Therefore, the secondary battery of the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.

[0030] The fifth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.

[0031] Beneficial effects of this application:

[0032] The present application provides a pre-lithiated negative electrode plate, a preparation method of a lithium replenishing composite layer, a lithium replenishing method, a secondary battery and an electronic device. The pre-lithiated negative electrode plate includes a negative electrode current collector and a negative electrode material layer. Along the thickness direction of the negative electrode plate, the negative electrode material layer includes a first surface and a second surface relative to each other. From the first surface to the second surface, the negative electrode material layer includes a first region, a second region and a third region in sequence, and the third region is located on the surface of the negative electrode current collector. The thickness of the first region accounts for 1 / 3 of the thickness of the negative electrode material layer, the thickness of the second region accounts for 1 / 3 of the thickness of the negative electrode material layer, and the thickness of the third region accounts for 1 / 3 of the thickness of the negative electrode material layer. Based on the mass of the first region, the mass percentage content of the lithium element is W1, based on the mass of the second region, the mass percentage content of the lithium element is W2, based on the mass of the third region, the mass percentage content of the lithium element is W3, W1>W2>W3, 1.01≤W1 / W2≤2.0, 1.01≤W2 / W3≤2.0. The pre-lithiated negative electrode plate meets the above characteristics, can improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity decay, and improve the energy density of the secondary battery.

[0033] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0035] Figure 1 A schematic diagram of the structure of a lithium-replenishing composite layer according to an embodiment of the present application;

[0036] Figure 2 A schematic diagram of the structure of a negative electrode plate and a lithium supplement composite layer during a pre-lithiation process of an implementation scheme of the present application;

[0037] Figure 3 A schematic diagram of the structure of a pre-lithiated negative electrode sheet according to an embodiment of the present application;

[0038] Figure 4 Schematic diagram of lithium replenishment area and interface area;

[0039] Figure 5 Schematic diagram of the total area of ​​the lithium replenishment zone and the total area of ​​the interface zone;

[0040] Figure 6 is the depth of the interface particles embedded in the lithium replenishment layer H a Schematic diagram;

[0041] Figure 7 is the height difference H between the upper surface of the interface layer and the lower surface of the interface layer c Schematic diagram. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0043] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0044] The first aspect of the present application provides a method for preparing a lithium supplement composite layer, which comprises the following steps:

[0045] (1) Under the condition of ambient temperature ≤30°C and humidity ≤1.7%, a lithium metal powder slurry is applied to a support layer and dried and rolled to form a lithium supplement layer; or a lithium foil and / or a lithium alloy foil is rolled to a support layer to form a lithium supplement layer; or a lithium or lithium alloy molten slurry is applied to a support layer and cooled and rolled to form a lithium supplement layer; wherein the roller pressure P1 is 0.1T / 10mm to 2T / 10mm; specifically, the roller pressure P11 of rolling after applying the lithium metal powder slurry to the support layer is 0.1T / 10mm to 2T / 10mm; the roller pressure P12 of rolling after the lithium foil and / or the lithium alloy foil is rolled to the support layer is 0.1T / 10mm to 2T / 10mm; the roller pressure P13 of rolling after applying the lithium or lithium alloy molten slurry to the support layer is 0.1T / 10mm to 2T / 10mm;

[0046] (2) Under the condition of ambient temperature ≤30°C and humidity ≤1.7%, the interface particles are coated on the surface of the lithium replenishing layer to form an interface layer, and then roller pressing is performed, the roller pressure P2 is 0.1T / 10mm to 2T / 10mm, preferably, the roller pressure P2 is 0.2T / 10mm to 0.8T / 10mm; the roller pressing temperature T1 is 25°C to 170°C, preferably, the roller pressing temperature T1 is 50°C to 120°C; the roller pressing standing time t1 is 5min to 50min, preferably, the roller pressing standing time t1 is 10min to 30min; and a lithium replenishing composite layer is formed.

[0047] Exemplarily, P1 may be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P11 may be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P12 can be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P13 can be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P2 can be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. T1 can be 25°C, 40°C, 50°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 170°C, or a range consisting of any two of the above values. t1 can be 5min, 9min, 10min, 15min, 19min, 20min, 25min, 29min, 30min, 35min, 39min, 40min, 45min, 49min, 50min, or a range consisting of any two of the above values.

[0048] In the present application, the lithium replenishing layer can be formed by coating and rolling a lithium metal powder slurry, or by rolling a lithium foil and / or a lithium alloy foil onto a support layer to form the lithium replenishing layer, or by coating a lithium or lithium alloy molten slurry onto a support layer and cooling and rolling to form the lithium replenishing layer. In the present application, the lithium alloy foil can include but is not limited to lithium aluminum alloy, and the lithium alloy in the lithium alloy molten slurry can include but is not limited to lithium aluminum alloy. The present application does not particularly limit the coating method of the interface particles on the surface of the lithium replenishing layer, as long as the purpose of the present application can be achieved. For example, the interface particles can be coated on the surface of the lithium replenishing layer by electrostatic spraying, roller coating or wiping.

[0049] In one embodiment of the present application, the lithium supplementation composite layer includes a support layer, a lithium supplementation layer and an interface layer, the lithium supplementation layer is arranged between the support layer and the interface layer, the interface layer includes interface particles, and the lithium supplementation layer includes at least one of lithium foil or lithium alloy foil. Specifically, Figure 1 As shown, the lithium supplement composite layer 10 includes a support layer 11, a lithium supplement layer 12 and an interface layer 13. The lithium supplement layer 12 is arranged between the support layer 11 and the interface layer 13. The interface layer 13 includes interface particles. The lithium supplement layer 12 includes at least one of lithium foil or lithium alloy foil.

[0050] The lithium supplement composite layer is prepared by the preparation method of the lithium supplement composite layer provided in the present application. The lithium supplement composite layer includes a support layer, a lithium supplement layer and an interface layer. The lithium supplement layer is arranged between the support layer and the interface layer. The interface layer has the ability to conduct electrons and ions. The interface layer is contacted with the negative electrode material layer, such as Figure 2 As shown, the interface layer 13 is brought into contact with the negative electrode material layer 15 disposed on the two surfaces of the negative electrode current collector 14. It can be understood that the above-mentioned "negative electrode material layer 15" refers to the negative electrode material layer of the negative electrode plate that has not been pre-lithiated; the lithium supplement layer and the negative electrode material layer form an internal short circuit, the lithium atoms in the lithium supplement layer undergo an oxidation reaction to lose electrons to generate lithium ions, the electrons and lithium ions are transferred to the surface or the inside of the negative electrode material layer through the interface layer, and the electrons and lithium ions undergo a reduction reaction in the negative electrode material layer to form a lithium intercalation compound, thereby realizing the pre-lithiation process of the negative electrode material layer. Since an interface layer is provided between the lithium supplement layer and the negative electrode material layer, the possibility of the lithium supplement layer adhering to the surface of the negative electrode material layer can be reduced, thereby reducing the side reactions that may occur due to the high activity of the lithium metal in the lithium supplement layer, thereby reducing the impact on the electrochemical performance of the secondary battery. After the pre-lithiation treatment is completed, the lithium supplement composite layer and the negative electrode plate are peeled off to obtain a pre-lithiated negative electrode plate. The above-mentioned peeling process can reduce the impact of the lithium metal single substance in the lithium supplement layer on the electrochemical performance of the secondary battery after it remains on the surface of the negative electrode material layer and enters the secondary battery, and the side reactions occur. The above method is used to prepare a lithium-replenishing composite layer, and then the negative electrode plate is pre-lithiated, which is beneficial to replenishing lithium for the negative electrode plate. The obtained pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0051] In one embodiment of the present application, the interface particles include at least one of a conductive agent or a lithium-intercalating material; the conductive agent includes at least one of conductive carbon black, carbon fiber, graphene or carbon nanotubes; the lithium-intercalating material includes at least one of artificial graphite, natural graphite, hard carbon, silicon-carbon material or silicon-oxygen material. In the present application, the conductive carbon black may include but is not limited to at least one of Super P, acetylene black or Ketjen black; the carbon fiber may include but is not limited to at least one of vapor-grown carbon fiber (VGCF) or nanocarbon fiber; the carbon nanotube may include but is not limited to at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or few-walled carbon nanotubes. By selecting the above-mentioned interface particles, the interface layer can have better electron and ion conductivity. In the pre-lithiation process, it is beneficial for electrons and lithium ions to be transferred to the surface or interior of the negative electrode material layer through the interface layer more quickly, which is beneficial for further replenishing lithium to the negative electrode plate, and can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0052] In one embodiment of the present application, the thickness H1 of the interface layer is 0.1 μm to 50 μm, preferably, the thickness H1 of the interface layer is 1 μm to 20 μm. Exemplarily, the value of H1 can be 0.1, 0.5, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range consisting of any two of the above values. The lithium atoms in the lithium replenishment layer lose electrons to form lithium ions, and the electrons and lithium ions are transferred to the surface or interior of the negative electrode material layer through the interface layer. By regulating the thickness of the interface layer within the scope of the present application, the interface layer has a suitable thickness, the transmission distance of electrons and lithium ions is moderate, and the electrons and lithium ions can effectively compound to form lithium-embedded compounds, which is beneficial to further replenish lithium to the negative electrode plate, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0053] In one embodiment of the present application, the coverage ratio s1 of the interface particles in the lithium replenishment layer is 50% to 100%. Preferably, the coverage ratio s1 of the interface particles in the lithium replenishment layer is 80% to 100%. Exemplarily, the value of s1 can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or a range consisting of any two of the above values. The coverage ratio of the interface layer in the lithium replenishment layer will affect the uniformity of lithium replenishment in the negative electrode material layer, that is, the greater the coverage ratio of the interface layer in the lithium replenishment layer, the higher the uniformity of lithium replenishment in the negative electrode material layer. The coverage ratio of the interface particles in the lithium replenishment layer is within the scope of the present application, the coverage ratio of the interface particles in the lithium replenishment layer is high, and the uniformity of lithium replenishment in the negative electrode material layer is high, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0054] In one embodiment of the present application, the interface particles are embedded in the lithium replenishing layer, and the depth of the interface particles embedded in the lithium replenishing layer accounts for 10% to 95% of the thickness of the interface layer. Preferably, the depth of the interface particles embedded in the lithium replenishing layer accounts for 20% to 70% of the thickness of the interface layer. Exemplarily, the ratio of the depth of the interface particles embedded in the lithium replenishing layer to the thickness of the interface layer can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or a range consisting of any two of the above values. When the interface particles are embedded in the lithium replenishing layer and the ratio of the depth of the interface particles embedded in the lithium replenishing layer to the thickness of the interface layer is within the scope of the present application, the lithium inside the lithium replenishing layer can be better promoted to participate in the oxidation reaction, thereby better transferring the lithium inside the lithium replenishing layer to the negative electrode material layer, which is beneficial to further replenish the negative electrode plate, can further improve the initial coulombic efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery; at the same time, it is also beneficial to the repeated use of the lithium replenishing composite layer.

[0055] In one embodiment of the present application, the thickness H2 of the lithium supplement layer is 0.001 mm to 1 mm, preferably, the thickness H2 of the lithium supplement layer is 0.005 mm to 0.1 mm. For example, the value of H2 can be 0.001, 0.003, 0.005, 0.007, 0.009, 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.3, 0.5, 0.7, 0.9, 1 or a range consisting of any two of the above values.

[0056] In one embodiment of the present application, the support layer includes at least one of metal foil, polyethylene terephthalate film, polypropylene film or polyethylene film, and the metal foil includes copper foil, nickel foil, steel foil or copper-nickel alloy foil. By selecting the above support layer, the support layer can provide better support for the lithium replenishment layer and the interface layer, improve the mechanical strength of the lithium replenishment composite layer, so that the lithium replenishment composite layer can be peeled off from the surface of the negative electrode material layer more smoothly after lithium replenishment, reduce the possibility of fracture of the lithium replenishment composite layer, and be beneficial to the lithium replenishment of the negative electrode plate, so as to further improve the initial coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0057] The present application has no particular limitation on the thickness H3 of the support layer, as long as the purpose of the present application can be achieved. For example, the thickness H3 of the support layer may be 3 μm to 50 μm, and preferably, the thickness H3 of the support layer may be 5 μm to 20 μm.

[0058] The second aspect of the present application provides a lithium supplementation method, which comprises the following steps:

[0059] The negative electrode plate is dried until the water content is ≤500ppm, the negative electrode plate comprising a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; it can be understood that the above-mentioned negative electrode plate refers to a negative electrode plate that has not been pre-lithiated. Under the conditions of ambient temperature of 25°C to 180°C and humidity ≤1.7%, any of the above-mentioned lithium-replenishing composite layers and the negative electrode plate are laminated so that the interface layer contacts the negative electrode material layer, and a pre-lithiation treatment is performed, wherein the interface pressure P3 between the interface layer and the negative electrode material layer is 0.1MPa to 2MPa, preferably, the interface pressure P3 between the interface layer and the negative electrode material layer is 0.2MPa to 1.0MPa; the lamination time t2 of the interface layer and the negative electrode material layer is 0.5h to 72h, preferably, the lamination time t2 of the interface layer and the negative electrode material layer is 1h to 48h; the lamination temperature T2 of the interface layer and the negative electrode material layer is 50°C to 180°C, preferably, the lamination temperature T2 of the interface layer and the negative electrode material layer is 60°C to 160°C; after the pre-lithiation treatment is completed, the lithium-replenishing composite layer and the negative electrode plate are peeled off to form a pre-lithiation negative electrode plate.

[0060] The present application has no particular restrictions on the manner in which the lithium-replenishing composite layer and the negative electrode sheet are bonded, as long as the purpose of the present application can be achieved. For example, the lithium-replenishing composite layer and the negative electrode sheet can be bonded by winding into a roll or pressing into a sheet. The present application has no particular restrictions on the method for regulating the interface pressure of bonding, as long as the purpose of the present application can be achieved. For example, when the lithium-replenishing composite layer and the negative electrode sheet are wound into a roll, the interface pressure between the interface layer and the negative electrode material layer can be regulated by regulating the winding tension. For example, when the lithium-replenishing composite layer and the negative electrode sheet are pressed into a sheet, the interface pressure between the interface layer and the negative electrode material layer can be regulated by regulating the pressing pressure.

[0061] For example, P3 can be 0.1MPa, 0.2MPa, 0.4MPa, 0.6MPa, 0.8MPa, 1.0MPa, 1.2MPa, 1.4MPa, 1.6MPa, 1.8MPa, 2MPa, or a range consisting of any two of the above values. t2 can be 0.5h, 1h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 48h, 50h, 55h, 60h, 65h, 70h, 72h, or a range consisting of any two of the above values. T2 can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, or a range consisting of any two of the above values.

[0062] The lithium-replenishing composite layer is prepared by the preparation method of the lithium-replenishing composite layer provided in the present application, and then the pre-lithiated negative electrode plate is prepared by the lithium-replenishing method provided in the present application, which is beneficial to replenishing lithium for the negative electrode plate. The obtained pre-lithiated negative electrode plate is applied to the secondary battery, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0063] The third aspect of the present application provides a pre-lithiated negative electrode sheet prepared according to any of the aforementioned lithium supplementation methods, the pre-lithiated negative electrode sheet comprising a negative electrode current collector and a negative electrode material layer, along the thickness direction of the negative electrode sheet, the negative electrode material layer comprises a first surface and a second surface relative to each other. From the first surface to the second surface, the negative electrode material layer comprises a first region, a second region and a third region in sequence, and the third region is located on the surface of the negative electrode current collector. The thickness of the first region accounts for 1 / 3 of the thickness of the negative electrode material layer, the thickness of the second region accounts for 1 / 3 of the thickness of the negative electrode material layer, and the thickness of the third region accounts for 1 / 3 of the thickness of the negative electrode material layer. Based on the mass of the first region, the mass percentage content of the lithium element is W1, based on the mass of the second region, the mass percentage content of the lithium element is W2, based on the mass of the third region, the mass percentage content of the lithium element is W3, W1>W2>W3, 1.01≤W1 / W2≤2.0, 1.01≤W2 / W3≤2.0. Exemplarily, W1 / W2 can be 1.01, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or a range consisting of any two of the above values; W2 / W3 can be 1.01, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or a range consisting of any two of the above values. In the present application, the pre-lithiated negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along the thickness direction of itself, or on two surfaces of the negative electrode current collector along the thickness direction of itself. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. The present application has no special restrictions as long as the purpose of the present application can be achieved. Exemplarily, such as Figure 3As shown, the pre-lithiation negative electrode sheet 100 includes a negative electrode current collector 14 and a negative electrode material layer 15 disposed on both surfaces of the negative electrode current collector 14. Along the thickness direction of the negative electrode sheet, that is, the Y direction, the negative electrode material layer 15 includes a first surface 1511 and a second surface 1522 that are opposite. From the first surface 1511 to the second surface 1522, the negative electrode material layer 15 includes a first region 151, a second region 152 and a third region 153 in sequence, and the third region 153 is located on the surface of the negative electrode current collector 14. The thickness of the first region 151 accounts for 1 / 3 of the thickness of the negative electrode material layer 15, the thickness of the second region 152 accounts for 1 / 3 of the thickness of the negative electrode material layer 15, and the thickness of the third region 153 accounts for 1 / 3 of the thickness of the negative electrode material layer 15. Based on the mass of the first region, the mass percentage of lithium is W1, based on the mass of the second region, the mass percentage of lithium is W2, based on the mass of the third region, the mass percentage of lithium is W3, W1>W2>W3, 1.01≤W1 / W2≤2.0, 1.01≤W2 / W3≤2.0. It can be understood that the "negative electrode material layer 15" in the above "pre-lithiated negative electrode plate 100 includes a negative electrode current collector 14 and a negative electrode material layer 15 disposed on both surfaces of the negative electrode current collector 14" refers to the negative electrode material layer after the negative electrode plate that has not been pre-lithiated has been pre-lithiated.

[0064] The present application has no particular restrictions on the manner of regulating the mass percentage of lithium elements in the first region, the second region, and the third region of the negative electrode material layer in the pre-lithiated negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the mass percentage of lithium elements in the first region, the second region, and the third region of the negative electrode material layer in the pre-lithiated negative electrode sheet can be regulated by regulating the pre-lithiation method. Exemplarily, the negative electrode sheet can be pre-lithiated by bonding a lithium-supplementing composite layer and a negative electrode sheet. For example, the amount of lithium replenishment and the rate of lithium replenishment can be regulated by regulating the interface pressure, bonding time, and bonding temperature of the interface layer of the lithium-supplementing composite layer and the negative electrode material layer, thereby regulating the mass percentage of lithium elements in the first region, the second region, and the third region of the negative electrode material layer in the pre-lithiated negative electrode sheet.

[0065] The present application has no particular restrictions on the method for regulating the value of W1 / W2, as long as the purpose of the present application can be achieved. By way of example, the value of W1 / W2 can be regulated by regulating the respective values ​​of W1 and W2, and the method for regulating W1 and W2 is as described above. The present application has no particular restrictions on the method for regulating the value of W2 / W3, as long as the purpose of the present application can be achieved. By way of example, the value of W2 / W3 can be regulated by regulating the respective values ​​of W2 and W3, and the method for regulating W2 and W3 is as described above.

[0066] The inventors have found that a negative electrode sheet that has not been pre-lithiated is taken, and the negative electrode sheet that has not been pre-lithiated includes a negative electrode current collector and a negative electrode material layer. The above-mentioned negative electrode sheet that has not been pre-lithiated is pre-lithiated to obtain a pre-lithiated negative electrode sheet. The negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a carbon material or a silicon-containing material. Within the same pre-lithiation treatment time, different negative electrode active materials have different lithium replenishment efficiencies. The amount of lithium replenishment of silicon-containing materials is relatively small, and the amount of lithium replenishment of carbon materials is relatively large. Therefore, different types of negative electrode active materials have different amounts of lithium replenishment of negative electrode active materials, and the amount of lithium replenishment in the obtained pre-lithiated negative electrode sheet is different. For the pre-lithiated negative electrode sheet, along the thickness direction of the negative electrode sheet, the negative electrode material layer includes a first surface and a second surface relative to each other; from the first surface to the second surface, the negative electrode material layer includes a first region, a second region and a third region in sequence, and the third region is located on the surface of the negative electrode current collector. The mass percentage of lithium elements in the first region, the second region and the third region satisfies: the mass percentage of lithium elements in the first region>the mass percentage of lithium elements in the second region>the mass percentage of lithium elements in the third region, and the ratio of the mass percentage of lithium elements in the first region to the mass percentage of lithium elements in the second region, and the ratio of the mass percentage of lithium elements in the second region to the mass percentage of lithium elements in the third region are within the scope of this application, the mass percentage of lithium elements in the first region, the mass percentage of lithium elements in the second region and the mass percentage of lithium elements in the third region are not 0, the lithium elements in the negative electrode material layer are distributed in a gradient along the thickness direction, and the pre-lithiated negative electrode plate has a higher amount of lithium supplement. The above-mentioned pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0067] In one embodiment of the present application, the negative electrode material layer includes a negative electrode active material, the negative electrode active material includes at least one of a carbon material or a silicon-containing material, the carbon material includes at least one of a graphite material or hard carbon, and the silicon-containing material includes at least one of a silicon-carbon material or a silicon-oxygen material. In the present application, the graphite material includes at least one of artificial graphite or natural graphite; the silicon-carbon material is a silicon-carbon composite material, and the mass percentage of the silicon element w based on the mass of the silicon-carbon composite material Si The mass percentage of carbon is 30% to 70%. C30% to 70%. The present application has no particular restrictions on the silicon-carbon composite material, as long as the purpose of the present application can be achieved. For example, the silicon-carbon composite material can be a composite material obtained by deposition. Exemplarily, the silicon-carbon composite material can be a silicon material deposited on a carbon skeleton, or a carbon material deposited on a silicon skeleton. Silicon-oxygen materials include SiOx, where 0<x<2. Exemplarily, the silicon-oxygen material can include silicon monoxide (SiO, with a molar ratio of silicon to oxygen of 1:1). The negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes the above-mentioned substances. The pre-lithiated negative electrode plate has a higher lithium supplement amount, and the prepared secondary battery has a higher first coulomb efficiency, a lower cycle capacity attenuation and a higher energy density.

[0068] In the present application, the negative electrode active material includes a carbon material and a silicon-containing substance. Based on the mass of the negative electrode active material, the mass percentage of the silicon-containing substance is W Si The mass percentage of the carbon material Wc is 5% to 100%, and the mass percentage of the carbon material Wc is 0 to 95%. For example, the mass percentage of the silicon-containing substance can be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, or a range consisting of any two of the above values; the mass percentage of the carbon material can be 0, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, or a range consisting of any two of the above values.

[0069] In one embodiment of the present application, the negative electrode active material only includes silicon-containing substances. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 18.6%≤w1≤63.5%, 11.5%≤W1≤18.4%, 9.2%≤W2<11.5%, 4.6%≤W3<9.2%. For example, w1 can be 18.6%, 25.5%, 30.5%, 37.5%, 38.5%, 39.5%, 40.5%, 41.5%, 42.5%, 43.5%, 44.5%, 45.5%, 46.5%, 47.5%, 55.5%, 63.5%, or a range consisting of any two of the above values; W2 can be 11.5%, 12.5%, 13.5%, 14.5%, 15.5%, 16.5%, 17.5%, 18.5%, 19.5%, 20.5%, 21.5%, 22.5%, 23.5%, 24.5%, 25.5%, 26.5%, 27.5%, 28.5%, 29.5%, 30.6%, 31.5%, 32.5%, 33.5%, 34.5%, 35.5%, 36.5%, 37.5%, 38.5%, 39.5%, 40.5%, 41.5%, 42.5%, 43.5%, 44.5%, 45.5%, 46.5%, 47.5%, 55.5%, 63.5%, or a range consisting of any two of the above values. 8.4% or a range consisting of any two of the above values; W2 can be 9.2%, 9.4%, 9.6%, 9.8%, 10%, 10.2%, 10.4%, 10.6%, 10.8%, 11%, 11.2%, 11.4% or a range consisting of any two of the above values; W3 can be 4.6%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.1% or a range consisting of any two of the above values. The negative electrode active material only includes silicon-containing substances, and the silicon-containing substances have a high gram capacity. The mass percentage values ​​of silicon element w1, W2, W3 in the negative electrode material layer are within the scope of this application. The capacity of the negative electrode material layer is high, and the ion conductivity and electronic conductivity are high. The pre-lithiated negative electrode plate has a high lithium supplement amount. Applying the above-mentioned pre-lithiated negative electrode plate to a secondary battery can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0070] In one embodiment of the present application, the negative electrode active material includes a carbon material and a silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of the silicon element in the negative electrode material layer is w1, 1.1%≤w1≤3.4%, 0.38%≤W1≤0.60%, 0.30%≤W2<0.38%, and 0.15%≤W3<0.30%. Exemplarily, w1 can be 1.1%, 1.5%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.4%, or a range consisting of any two of the above values; W1 can be 0.38%, 0.4%, 0.42%, 0.44%, 0.46%, 0.48%, 0.5%, 0.52%, 0.54%, 0.56%. , 0.58%, 0.60% or a range consisting of any two of the above values; W2 can be 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37% or a range consisting of any two of the above values; W3 can be 0.15%, 0.17%, 0.19%, 0.2%, 0.21%, 0.23%, 0.25%, 0.27%, 0.29% or a range consisting of any two of the above values. The negative electrode active material includes carbon material and silicon-containing material. During the same pre-lithiation treatment time, the lithium replenishment efficiency of different negative electrode active materials is different. The lithium replenishment amount of silicon-containing material is relatively small, and the lithium replenishment amount of carbon material is relatively large, which will affect the lithium replenishment amount in the pre-lithiation negative electrode plate. The values ​​of the mass percentage w1, W1, W2, and W3 of the silicon element in the negative electrode material layer are within the scope of this application. The carbon material and the silicon-containing substance have a suitable mass percentage. The negative electrode active material has a higher capacity and a higher lithium replenishment amount, which can make the pre-lithiated negative electrode plate have a higher capacity and a higher lithium replenishment amount. Applying the above-mentioned pre-lithiated negative electrode plate to a secondary battery can further improve the first coulombic efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0071] In one embodiment of the present application, the negative electrode active material includes a carbon material and a silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of the silicon element in the negative electrode material layer is w1, 3.3%≤w1≤10.2%, 2.8%≤W1≤4.5%, 2.2%≤W2<2.8%, 1.1%≤W3<2.2%. Exemplarily, w1 can be 3.3%, 4%, 4.5%, 5%, 5.7%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 9.6%, 10%, 10.2%, or a range consisting of any two of the above values; W1 can be 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.5%, or a range consisting of any two of the above values; W2 can be 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, or a range consisting of any two of the above values; W3 can be 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, or a range consisting of any two of the above values. The negative electrode active materials include carbon materials and silicon-containing substances. Within the same pre-lithiation treatment time, the lithium replenishment efficiency of different negative electrode active materials is different. The lithium replenishment amount of silicon-containing substances is relatively small, and the lithium replenishment amount of carbon materials is relatively large, which will affect the lithium replenishment amount in the pre-lithiation negative electrode plate. The values ​​of the mass percentage of silicon element w1, W2, W3 in the negative electrode material layer are within the scope of this application. The carbon material and the silicon-containing substance have a suitable mass percentage. The negative electrode active material has a higher capacity and a higher lithium replenishment amount, which can make the pre-lithiation negative electrode plate have a higher capacity and a higher lithium replenishment amount. Applying the above-mentioned pre-lithiation negative electrode plate to a secondary battery can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0072] In one embodiment of the present application, the porosity of the first region is S1, the porosity of the second region is S2, and the porosity of the third region is S3, S1>S2>S3. S1, S2 and S3 satisfy the above-mentioned size relationship, which is conducive to the migration of lithium ions along the thickness direction of the negative electrode sheet, and can improve the kinetic performance of the negative electrode sheet. The present application has no particular restrictions on the manner of regulating the porosity of the first region, the second region and the third region of the negative electrode material layer in the pre-lithiated negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the amount of lithium replenishment and the rate of lithium replenishment can be regulated by regulating the interface pressure, bonding time and bonding temperature of the interface layer of the lithium replenishment composite layer and the negative electrode material layer, thereby regulating the amount of lithium replenishment in the first region, the second region and the third region of the negative electrode material layer in the pre-lithiated negative electrode sheet, and then regulating the porosity of the first region, the second region and the third region.

[0073] In one embodiment of the present application, 1.01≤S1 / S2≤1.5, 1.01≤S2 / S3≤1.5. Exemplarily, S1 / S2 can be 1.01, 1.1, 1.2, 1.3, 1.4, 1.5 or a range consisting of any two of the above values; S2 / S3 can be 1.01, 1.1, 1.2, 1.3, 1.4, 1.5 or a range consisting of any two of the above values. The values ​​of S1 / S2 and S2 / S3 are within the scope of the present application, and the porosity of the first region is greater than the porosity of the second region and the porosity of the third region, which is conducive to the migration of lithium ions along the thickness direction of the negative electrode sheet and can further improve the kinetic performance of the negative electrode sheet. The present application does not particularly limit the method for regulating the value of S1 / S2, as long as the purpose of the present application can be achieved. Exemplarily, the value of S1 / S2 can be regulated by regulating the respective values ​​of S1 and S2, and the regulation method of S1 and S2 is as described above. The present application has no particular restrictions on the method for regulating the value of S2 / S3, as long as the purpose of the present application can be achieved. Exemplarily, the value of S2 / S3 can be regulated by regulating the respective values ​​of S2 and S3, and the method for regulating S2 and S3 is as described above.

[0074] In one embodiment of the present application, the negative electrode active material only includes silicon-containing substances. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 18.6%≤w1≤63.5%, 42.1%≤S1≤57.0%, 38.0%≤S2<42.1%, 25.0%≤S3<38.0%. Exemplarily, w1 may be 18.6%, 25.5%, 37.5%, 38.5%, 39.5%, 40.5%, 41.5%, 42.5%, 43.5%, 44.5%, 45.5%, 46.5%, 47.5%, 55.5%, 63.5%, or a range consisting of any two of the above values; S1 may be 42.1%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 57.0%, or a range consisting of any two of the above values; S 2 can be 38.0%, 38.5%, 39.0%, 39.5%, 40.0%, 40.5%, 41.0%, 41.5%, 42.0% or a range consisting of any two of the above values; S3 can be 25.0%, 26.0%, 27.0%, 28.0%, 29.0%, 30.0%, 31.0%, 32.0%, 33.0%, 34.0%, 35.0%, 36.0%, 37.0%, 37.9% or a range consisting of any two of the above values. The negative electrode active material only includes silicon-containing substances, and the silicon-containing substances have a high gram capacity. The mass percentage content of silicon element w1, S1, S2, and S3 in the negative electrode material layer is within the scope of this application, which is conducive to the migration of lithium ions along the thickness direction of the negative electrode sheet, and can further improve the kinetic performance of the negative electrode sheet. At the same time, the negative electrode sheet has a high capacity.

[0075] In one embodiment of the present application, the negative electrode active material includes a carbon material and a silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 1.1%≤w1≤3.4%, 26.3%≤S1≤35.5%, 23.7%≤S2<26.3%, and 15.8%≤S3<23.7%. Exemplarily, w1 can be 1.1%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.4% or a range consisting of any two of the above values; S1 can be 26.3%, 27.3%, 28.3%, 29.3%, 30.3%, 31.3%, 32.3%, 33.3%, 34.3 %, 35.3%, 35.5% or a range consisting of any two of the above values; S2 can be 23.7%, 24%, 24.7%, 25%, 25.7%, 26%, 26.2% or a range consisting of any two of the above values; S3 can be 15.8%, 16.8%, 17.8%, 18.8%, 19.8%, 20.8%, 21.8%, 22.8%, 23.6% or a range consisting of any two of the above values. The negative electrode active material includes carbon materials and silicon-containing substances, which is beneficial to further improve the gram capacity and lithium replenishment of the negative electrode active material. The mass percentage of silicon element w1, S1, S2, and S3 in the negative electrode material layer is within the scope of this application, which is beneficial to the migration of lithium ions along the thickness direction of the negative electrode plate, and can further improve the kinetic performance of the negative electrode plate. At the same time, the negative electrode plate has a higher capacity.

[0076] In one embodiment of the present application, the negative electrode active material includes a carbon material and a silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 3.3%≤w1≤10.2%, 31.6%≤S1≤42.6%, 28.4%≤S2<31.6%, and 18.9%≤S3<28.4%. Exemplarily, w1 can be 3.3%, 4.5%, 5.7%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 9.6%, 10%, 10.2% or a range consisting of any two of the above values; S1 can be 31.6%, 32.6%, 33.6%, 34.6%, 35.6%, 36.6%, 37.6%, 38.6%, 39.6%, 40.6%, 41.6%, 42.6% Or a range consisting of any two of the above values; S2 can be 28.4%, 29%, 29.4%, 30%, 30.4%, 31%, 31.4%, 31.5% or a range consisting of any two of the above values; S3 can be 18.9%, 19.9%, 20.9%, 21.9%, 22.9%, 23.9%, 24.9%, 25.9%, 26.9%, 27.9%, 28.3% or a range consisting of any two of the above values. The negative electrode active material includes carbon materials and silicon-containing substances, which is beneficial to further improve the gram capacity and lithium replenishment of the negative electrode active material. The mass percentage of silicon element w1, S1, S2, and S3 in the negative electrode material layer is within the scope of this application, which is beneficial to the migration of lithium ions along the thickness direction of the negative electrode plate, and can further improve the kinetic performance of the negative electrode plate. At the same time, the negative electrode plate has a higher capacity.

[0077] In the present application, the negative electrode material layer also includes a negative electrode binder and a negative electrode conductor. The present application does not particularly limit the type of negative electrode binder, as long as the purpose of the present application can be achieved, for example, the negative electrode binder may include polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene-butadiene rubber, SBR), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, lithium carboxymethyl cellulose, lithium polyacrylate, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The present application does not particularly limit the type of negative electrode conductor, as long as the purpose of the present application can be achieved, for example, the negative electrode conductor may include but is not limited to at least one of conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application has no particular restrictions on the mass ratio of the negative electrode active material, the negative electrode binder and the negative electrode conductive agent in the negative electrode material layer. Those skilled in the art may select according to actual needs as long as the purpose of the present application can be achieved.

[0078] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector (such as a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.), etc.

[0079] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 4 μm to 20 μm. The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided negative electrode material layer is 30 μm to 250 μm.

[0080] The fourth aspect of the present application provides a secondary battery, which includes the pre-lithiated negative electrode plate in any of the above embodiments. Therefore, the secondary battery of the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.

[0081] In the present application, the secondary battery also includes a positive electrode plate. The positive electrode plate includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive current collector" means that the positive electrode material layer can be disposed on one surface of the positive current collector along its own thickness direction, or on two surfaces of the positive current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the positive current collector or a partial area of ​​the positive current collector. This application is not particularly limited as long as the purpose of this application can be achieved.

[0082] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).

[0083] The positive electrode material layer of the present application includes a positive electrode active material, and the positive electrode active material includes a substance that can reversibly embed and extract active ions such as lithium ions. The positive electrode material layer can be one layer or more layers, and each layer in the multi-layer positive electrode material layer can contain the same or different positive electrode active materials. The present application has no special restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. At least one of the above-mentioned lithium nickel cobalt manganese oxide may include LiNi 0.95 Co 0.03 Mn 0.02 O2(Ni95),LiNi 0.91 Co 0.03 Mn 0.06 O2(Ni91), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523) or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3At least one of O2 (NCM111). The positive electrode material layer of the present application also includes a positive electrode conductor and a positive electrode binder. The present application has no special restrictions on the positive electrode conductor and the positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor in the positive electrode material layer may include at least one of the above-mentioned negative electrode conductors; the positive electrode binder in the positive electrode material layer may include at least one of the above-mentioned negative electrode binders. The present application has no special restrictions on the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0084] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode current collector is 6 μm to 25 μm. The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided positive electrode material layer is 25 μm to 250 μm.

[0085] In the present application, the secondary battery also includes an electrolyte. The electrolyte includes a lithium salt. The present application has no particular restrictions on the type of lithium salt, and lithium salts known in the art can be used. For example, the lithium salt may include but is not limited to lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiN(CF3SO2)2, LiTFSI), lithium bis(fluorosulfonyl)imide (Li(N(SO2F)2), LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalate borate) (LiB(C2O4)2, LiBOB) or lithium difluorooxalate borate (LiBF2(C2O4), LiDFOB). The present application has no particular restrictions on the mass percentage of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The electrolyte also includes a non-aqueous organic solvent. The present application has no particular restrictions on the non-aqueous organic solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous organic solvent may contain at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), vinylene carbonate, propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned fluorinated carbonate compound may include but is not limited to fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include, but are not limited to, at least one of 1,3-propanesultone, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester.The present application has no particular limitation on the mass percentage of the non-aqueous organic solvent in the electrolyte, as long as the purpose of the present application can be achieved.

[0086] In the present application, the secondary battery also includes a diaphragm. The diaphragm is used to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0087] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a diaphragm binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned diaphragm binder, for example, it may be at least one of the aforementioned negative electrode binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or vinylidene fluoride-hexafluoropropylene copolymer.

[0088] The secondary battery of the present application also includes a packaging bag for containing a positive electrode plate, a separator, a pre-lithiated negative electrode plate and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.

[0089] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0090] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no special restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the pre-lithiated negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode sheet, the separator and the pre-lithiated negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection components, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0091] The fifth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.

[0092] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0093] Example

[0094] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0095] Test methods and equipment:

[0096] The mass percentage test of lithium element in the first area, the second area and the third area:

[0097] Take the pre-lithiation negative electrode sheet, and use a blade to scrape the negative electrode material of the surface 1 / 3 thickness, the middle 1 / 3 thickness, and the bottom 1 / 3 thickness along the thickness direction of the negative electrode sheet, as the negative electrode material of the first region, the second region, and the third region respectively.

[0098] The mass percentage of lithium in the negative electrode material of the first region, the second region and the third region was detected by inductively coupled plasma-optical emission spectrometry (ICP-OES). The ICP-OES used was a PE7000DV spectrometer produced by PerkinElmer, USA. The test conditions of ICP-OES were: radio frequency (RF) of 40.68 MHz, RF power of 1300 W, argon secondary pressure of 0.6 MPa, auxiliary gas flow of 0.2 L / min, cooling gas flow of 15 L / min, and pump speed of 1.5 mL / min.

[0099] Test of the mass percentage of silicon in the negative electrode material layer:

[0100] Take the pre-lithiation negative electrode sheet, scrape the negative electrode material on the surface of the negative electrode current collector with a blade, and detect the mass percentage of silicon element in the negative electrode material by inductively coupled plasma-optical emission spectrometer (ICP-OES). The ICP-OES used is a PE7000DV spectrometer produced by PerkinElmer, USA. The test conditions of ICP-OES are: radio frequency (RF) is 40.68MHz, radio frequency power is 1300W, argon secondary pressure is 0.6MPa, auxiliary gas flow rate is 0.2L / min, cooling gas flow rate is 15L / min, and pump speed is 1.5mL / min.

[0101] Porosity test of the first, second and third areas:

[0102] (1) Total porosity (S1+S2+S3) test of negative electrode material layer:

[0103] a) Sample preparation: Take the pre-lithiated negative electrode sheet, wrap it with weighing paper on the top and bottom, lay it flat on the die, and punch it with a punch to obtain 40 disc samples with a diameter of 16 mm. Test the thickness of the disc samples and take the average value h1.

[0104] b) Test: Place 40 disc samples obtained in step a) into the sample cup of a true density instrument (AccuPycⅡ1340), tighten the lid, test three times, take the average value of the test results and record it as the true volume V2 of the disc sample, and record the test temperature.

[0105] c) Result analysis: Apparent volume V1 = s × h1 × number of disc samples, where s is the surface area of ​​the disc sample and h1 is the thickness of the disc sample; the porosity of the disc sample is obtained according to Porosity (Porosity) = (V1-V2) / V1×100%, which is S1+S2+S3.

[0106] (2) Total porosity (S2+S3) test of the second and third regions:

[0107] a) Sample preparation: Take the disc sample after the test in step (1), scrape off 1 / 3 of the thickness of the negative electrode material on the surface with a blade, and measure the thickness of the disc sample, and take the average value h 1-1 .

[0108] b) Test: Place the 40 disc samples obtained in step a) into the sample cup of a true density instrument (AccuPycⅡ1340), tighten the lid, test three times, and take the average value of the test results, which is recorded as the true volume V of the disc sample. 2-1 , and record the test temperature.

[0109] c) Result analysis: Apparent volume V 1-1 =s×h 1-1 × number of disc samples, where s is the surface area of ​​the disc sample, h is 1-1 is the thickness of the disc sample; according to the porosity (Porosity) = (V 1-1 -V 2-1 ) / V 1-1 ×100% to obtain the porosity of the disc sample, which is S2+S3.

[0110] (3) Porosity test of the third region (S3):

[0111] a) Sample preparation: Take the disc sample after the test in step (2), scrape off 1 / 3 of the thickness of the negative electrode material on the surface with a blade, and measure the thickness of the disc sample, and take the average value h 1-2 .

[0112] b) Test: Place the 40 disc samples obtained in step a) into the sample cup of a true density instrument (AccuPycⅡ1340), tighten the lid, test three times, and take the average value of the test results, which is recorded as the true volume V of the disc sample. 2-2 , and record the test temperature.

[0113] c) Result analysis: Apparent volume V 1-2 =s×h 1-2 × number of disc samples, where s is the surface area of ​​the disc sample, h is 1-2 is the thickness of the disc sample; according to the porosity (Porosity) = (V 1-2-V 2-2 ) / V 1-2 ×100% to obtain the porosity of the disc sample, which is S3.

[0114] (4) Calculation of the porosity of the first region and the porosity of the second region:

[0115] Porosity of the first region S1 (%) = (S1 + S2 + S3) - (S2 + S3);

[0116] The porosity of the second region S2 (%) = (S2 + S3) - S3.

[0117] Thickness test of support layer, lithium supplement layer and interface layer:

[0118] Place the sample to be tested on the table, level it, and measure its thickness data as required. Use non-woven fabric to wipe the measuring end face of the micrometer; press the measuring linkage mechanism to make the two measuring end faces completely contact, and press the "zero" key; the two measuring end faces of the micrometer are in contact with the end face of the sample to be tested, read the displayed data, and record the readings. Measure at intervals of 70mm perpendicular to the tape running direction (ie TD direction), and at intervals of 100mm along the tape running direction (ie MD direction); test 12 points along the TD direction of the sample to be tested; test 12 points along the MD direction of the sample to be tested; test a total of 24 points; take the average value of the thickness of the 24 points as the thickness of the sample to be tested.

[0119] The support layer is used as the sample to be tested, and the thickness H3 of the support layer is obtained.

[0120] The support layer and the lithium supplement layer are combined as the sample to be tested, and the total thickness H of the support layer and the lithium supplement layer is obtained. 支撑层&补锂层 ; The total thickness of the support layer and the lithium supplement layer H 支撑层&补锂层 The difference between the thickness H3 of the support layer and the thickness H2 of the lithium supplement layer is H2, that is, H2 = H 支撑层&补锂层 -H3.

[0121] The support layer, lithium supplement layer and interface layer are composited as the sample to be tested, and the total thickness H of the support layer, lithium supplement layer and interface layer is obtained. 支撑层&补锂层&界面层 , the thickness of the interface layer is H1, that is, H1 = H 支撑层&补锂层&界面层 -H 支撑层&补锂层 .

[0122] Test of coverage ratio of interface particles in lithium replenishment layer:

[0123] (1) Place the sample flat on the sample stage and then use an optical microscope to magnify and photograph the sample (Keyence VHX-7000, magnification 300 times).

[0124] (2) The photographed images were imported into the image processing software IMAGE J, and the lithium replenishment area and the interface area were distinguished by threshold value, and the area of ​​each interface area S1 to S n The total area of ​​the interface zone is Sinterface = S1+S2+S3+…+S n-1 +S n ; Measure the length L and width W of the lithium replenishment area, and calculate the total area of ​​the lithium replenishment area S replenishment = W × L; then the coverage ratio of the interface particles in the lithium replenishment layer s1 = S interface / S replenishment. Figure 4 and Figure 5 shown.

[0125] (3) Twelve parallel samples were tested for each sample, and the average value of the 12 s1 was taken as the coverage ratio of the interface particles in the lithium replenishment layer.

[0126] Test on the ratio of the depth of interface particles embedded in the lithium supplement layer to the thickness of the interface layer:

[0127] (1) Sample preparation: The lithium-replenishing composite layer sample was cut into a size of 6 mm × 6 mm and glued to the sample stage with conductive glue. Then, the lithium-replenishing composite layer sample was cross-section polished using a cross section polisher (model IB-19520CCP). The polishing conditions were: vacuum degree of 10 -3 Pa, the accelerating voltage is 6 kV, and the polishing speed is 500 μm / h.

[0128] (2) Parameter test: The polished sample was placed on the sample stage of a scanning electron microscope and its cross section was tested using a scanning electron microscope (SEM, Scanning electron microscope, model: Thermo Fisher Scientific FEI-Apreo S). The test conditions were: acceleration voltage of 10 kV, grating of 10 spot, working distance of 10 mm, and magnification of 2000 times.

[0129] The depth of interfacial particles embedded in the lithium replenishment layer H a It is defined as: the height difference between the upper surface of the lithium supplement layer and the lower surface of the interface layer, as follows Figure 6 As shown. c It is defined as: the height difference between the upper surface of the interface layer and the lower surface of the interface layer, as shown in Figure 7 As shown. Define h=H a / H c Each sample was tested with 12 parallel samples, and the average value of 12 h was taken as the ratio of the depth of the interface particles embedded in the lithium replenishment layer to the thickness of the interface layer.

[0130] First coulombic efficiency test:

[0131] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: charge the lithium-ion battery in the embodiment or comparative example at 25°C at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, stand for 5 minutes, and then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V. The capacity of the above charging process is recorded as C0, and the capacity of the above discharging process is recorded as C1. The first coulomb efficiency is calculated according to the following formula.

[0132] First coulombic efficiency (%) = C1 / C0×100%.

[0133] Cycle performance test:

[0134] The voltage range marked on the factory battery packaging shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, the lithium-ion battery in the embodiment or comparative example is charged and discharged for the first time, charged at a constant current of 0.2C to a cut-off voltage of 4.45V, and then charged at a constant voltage of 4.45V until the current is less than 0.05C, and after standing for 5 minutes, discharged at a constant current of 0.2C to a cut-off voltage of 3.0V, and the discharge capacity of the lithium-ion battery is measured to be A; then, 400 charging and discharging cycles are performed according to the above steps in an environment of 25°C, and the discharge capacity of the lithium-ion battery at the 400th time is measured to be B, and the cycle capacity retention rate is calculated according to the following formula.

[0135] Cycle capacity retention rate (%) = B / A × 100%.

[0136] The larger the value of the cycle capacity retention rate obtained from the test, the better the cycle performance of the lithium-ion battery.

[0137] Energy density test:

[0138] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, charge the lithium-ion battery in the embodiment or comparative example at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, let it stand for 5 minutes, then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V, and let it stand for 5 minutes. The energy of the above discharge process is recorded as the discharge energy E. Calculate the volume V (mm) of the lithium-ion battery 3 ) = length × width × height.

[0139] Energy density (Wh / L) = E / V × 10 6 .

[0140] Example 1-1

[0141] <Preparation of lithium-supplementing composite layer>

[0142] Under the conditions of ambient temperature of 25°C and humidity of 1.0%, the lithium foil was rolled into a copper foil support layer with a thickness of 14 μm to form a lithium supplement layer. The roller pressure P12 was 1.5T / 10mm to obtain a lithium supplement layer / support layer composite structure.

[0143] Under the condition of ambient temperature of 25°C and humidity of 1.0%, the interface particles of artificial graphite are coated on the surface of the lithium supplement layer by rubbing to form an interface layer, and then roller pressing is performed, the roller pressure P2 is 0.5T / 10mm, the roller pressing temperature T1 is 90°C, and the roller pressing standing time t1 is 30min to form a lithium supplement composite layer. Among them, the thickness H1 of the interface layer in the lithium supplement composite layer is 8μm, the thickness H2 of the lithium supplement layer is 0.03mm, the coverage ratio s1 of the interface particles in the lithium supplement layer is 85%, and the depth of the interface particles embedded in the lithium supplement layer accounts for 50% of the thickness of the interface layer.

[0144] <Preparation of negative electrode sheet>

[0145] The negative electrode active material silicon carbon material, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber (SBR), and the negative electrode binder lithium carboxymethyl cellulose are mixed in a weight ratio of 85:5:5:5, and deionized water is added as a solvent, and the mixture is stirred and mixed to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 28wt%; the negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 90°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. Dry under vacuum conditions at 90°C for 1h, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 51mm×44.2mm is obtained. Among them, the silicon-carbon material is a silicon-carbon composite material. Based on the mass of the silicon-carbon composite material, the mass percentage of silicon element w Si The mass percentage of carbon is 50%. C 50%; the surface density CW of the negative electrode material layer is 2.3 mg / cm 2 The compaction density of the cold pressing process is 1.0g / cm 3 .

[0146] <Preparation of pre-lithiated negative electrode sheet>

[0147] The prepared negative electrode sheet is dried until the water content is ≤500ppm; under the condition of ambient temperature of 90°C and humidity of 1.0%, the prepared lithium-replenishing composite layer is laminated with the prepared negative electrode sheet so that the interface layer contacts the negative electrode material layer, and the lamination method is to press the sheet into a sheet, and the pre-lithiation treatment is performed, the interface pressure P3 between the interface layer and the negative electrode material layer is 0.6MPa, the lamination time t2 between the interface layer and the negative electrode material layer is 20h, and the lamination temperature T2 between the interface layer and the negative electrode material layer is 90°C. After the pre-lithiation treatment, the lithium-replenishing composite layer is peeled off from the negative electrode sheet to form a pre-lithiation negative electrode sheet. Based on the mass of the first region, the mass percentage content W1 of the lithium element is 16.5%; based on the mass of the second region, the mass percentage content W2 of the lithium element is 10.5%; based on the mass of the third region, the mass percentage content W3 of the lithium element is 6.5%, W1>W2>W3.

[0148] <Preparation of positive electrode sheet>

[0149] The positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode conductive agent acetylene black, and the positive electrode binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is stirred and mixed to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 110°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 110°C for 1h, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 48mm×41.2mm is obtained. Among them, the surface density of the positive electrode material layer is 19.0mg / cm 2 The compaction density of the cold pressing process is 4.15g / cm 3 .

[0150] <Preparation of Electrolyte>

[0151] In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and ethyl propionate (EP) were mixed in a weight ratio of 3:1:3:3 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 was 12.5%, and the remainder was the base solvent.

[0152] <Preparation of Separator>

[0153] A porous polypropylene film with a thickness of 5 μm (provided by Celgard Company) was used as a separator.

[0154] <Preparation of lithium-ion batteries>

[0155] The prepared positive electrode sheet, separator, pre-lithiated negative electrode sheet and separator are stacked in order, so that the separator is placed between the positive electrode sheet and the pre-lithiated negative electrode sheet to play an isolating role, and the electrode assembly is wound. After welding the pole ear, the electrode assembly is placed in an aluminum plastic film packaging bag, placed in an 85°C vacuum oven for 12 hours to remove moisture, and the electrolyte is injected. After vacuum packaging, standing, formation (charging to 3.5V at a constant current of 0.02C, and then charging to 3.9V at a constant current of 0.1C), degassing, trimming, and capacity processing steps, a lithium-ion battery is obtained.

[0156] Example 1-2 to Example 1-5

[0157] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1. Among them, the sum of the mass percentages of the negative electrode active material, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber and the negative electrode binder lithium carboxymethyl cellulose is 100%, and the mass ratio of the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber and the negative electrode binder lithium carboxymethyl cellulose remains unchanged.

[0158] Examples 1-6

[0159] In the preparation of negative electrode sheet, the negative electrode active material is a mixture of silicon-containing silicon-carbon material and carbon material artificial graphite. Based on the mass of the negative electrode active material, the mass percentage of silicon-containing material is W Si The silicon-carbon material is a silicon-carbon composite material, and based on the mass of the silicon-carbon composite material, the mass percentage of silicon element wsi is 30%, and the mass percentage of carbon element wc is 70%, and the rest is the same as Example 1-1. Among them, the sum of the mass percentages of the negative electrode active material, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber and the negative electrode binder lithium carboxymethyl cellulose is 100%, and the mass ratio of the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber and the negative electrode binder lithium carboxymethyl cellulose remains unchanged.

[0160] Example 1-7 to Example 1-11

[0161] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-6. Among them, the sum of the mass percentages of the negative electrode active material, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber and the negative electrode binder lithium carboxymethyl cellulose is 100%, and the mass ratio of the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber and the negative electrode binder lithium carboxymethyl cellulose remains unchanged.

[0162] Examples 1-12

[0163] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0164] Examples 1-13

[0165] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-10.

[0166] Example 2-1 to Example 2-11

[0167] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1.

[0168] Example 2-12

[0169] Except that the relevant preparation parameters are adjusted according to Table 3 and the thickness H1 of the interface layer in the lithium supplementing composite layer is 2 μm, the rest is the same as Example 1-1.

[0170] Example 2-13 to Example 2-14

[0171] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1.

[0172] Comparative Example 1-1

[0173] Except that no interface layer is provided in <Preparation of lithium supplementing composite layer>, the rest is the same as Example 1-1.

[0174] Comparative Example 2-1 to Comparative Example 2-5

[0175] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1.

[0176] The preparation parameters and electrical performance parameters of each embodiment and comparative example are shown in Tables 1 to 3.

[0177] Table 1

[0178]

[0179]

[0180] Note: In Table 1, “ / ” indicates no relevant preparation parameters.

[0181] Table 2

[0182] First coulombic efficiency (%) Cycle capacity retention rate (%) Energy density (Wh / L) Example 1-1 92.5 90.5 854.4 Example 1-2 91.0 85.0 825.0 Examples 1-3 92.9 84.0 840.0 Examples 1-4 92.0 91.0 830.0 Examples 1-5 92.7 85.0 860.0 Examples 1-6 92.5 87.0 753.0 Examples 1-7 93.5 92.5 784.4 Examples 1-8 94.0 86.0 770.0 Examples 1-9 92.0 86.0 785.0 Examples 1-10 93.0 91.5 804.3 Embodiment 1-11 93.4 87.0 795.0 Examples 1-12 90.8 87.9 823.1 Examples 1-13 92.0 92.5 800.0 Comparative Example 1-1 78.2 76.5 722.5

[0183] From Examples 1-1 to 1-13 and Comparative Example 1-1, it can be seen that the lithium replenishing composite layer is prepared by the preparation method of the lithium replenishing composite layer provided in the present application, and then the pre-lithiated negative electrode plate is prepared by the lithium replenishing method provided in the present application, and the pre-lithiated negative electrode plate is applied to the lithium ion battery, and the prepared lithium ion battery has a high first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the lithium ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium ion battery can be improved. In Comparative Example 1-1, the preparation method of the lithium replenishing composite layer is not within the scope of the present application, and the prepared lithium ion battery has a low first coulombic efficiency, cycle capacity retention rate and energy density.

[0184] It can be seen from Examples 1-1 to 1-3 that the negative electrode active material only includes silicon-containing substances, the mass percentage of the negative electrode active material in the negative electrode material layer increases, and the mass percentage of the silicon element in the silicon-carbon material increases, the mass percentage of the silicon element in the negative electrode material layer increases, the porosity of the first region, the second region, and the third region increases, and the better the kinetic performance of the pre-lithiated negative electrode plate, the more conducive to the transmission of lithium ions from top to bottom during lithium replenishment.

[0185] It can be seen from Examples 1-1, 1-4 and 1-5 that the mass percentage of the negative electrode active material in the negative electrode material layer remains unchanged, and the mass percentage of the silicon element in the silicon-carbon material increases, which is more conducive to replenishing lithium on the surface.

[0186] The values ​​of W1 / W2 and W2 / W3 usually affect the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. From Examples 1-1 to 1-13, it can be seen that the values ​​of W1 / W2 and W2 / W3 are within the scope of this application, and the prepared lithium-ion batteries have higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that the initial coulombic efficiency of lithium-ion batteries can be improved, the cycle capacity attenuation can be reduced, and the energy density of lithium-ion batteries can be improved.

[0187] The type of negative electrode active material usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. From Examples 1-1, 1-7 and 1-10, or, 1-2, 1-6 and 1-9, or, 1-3, 1-8 and 1-11, it can be seen that the type of negative electrode active material is within the scope of this application, and the prepared lithium-ion battery has a higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that the initial coulombic efficiency of lithium-ion batteries can be improved, the cycle capacity attenuation can be reduced, and the energy density of lithium-ion batteries can be improved.

[0188] The values ​​of S1 / S2 and S2 / S3 usually affect the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. From Examples 1-1 to 1-13, it can be seen that the values ​​of S1 / S2 and S2 / S3 are within the scope of this application, and the prepared lithium-ion batteries have higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that the initial coulombic efficiency of lithium-ion batteries can be improved, the cycle capacity attenuation can be reduced, and the energy density of lithium-ion batteries can be improved.

[0189] Table 3

[0190]

[0191]

[0192] Note: (1) In Table 3, in Examples 2-13, "Interface Particle Type" is "97% artificial graphite + 3% single-walled carbon nanotubes", indicating that the interface particles include artificial graphite and single-walled carbon nanotubes. Based on the mass of the interface particles, the mass percentage of artificial graphite is 97%, and the mass percentage of single-walled carbon nanotubes is 3%.

[0193] From Examples 2-1 to 2-14 and Comparative Examples 2-1 to 2-5, it can be seen that the lithium replenishing composite layer is prepared by the preparation method of the lithium replenishing composite layer provided in the present application, and then the pre-lithiated negative electrode plate is prepared by the lithium replenishing method provided in the present application, and the pre-lithiated negative electrode plate is applied to the lithium ion battery, and the prepared lithium ion battery has a high first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the lithium ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium ion battery can be improved. In Comparative Examples 2-1 to 2-5, the preparation method of the lithium replenishing composite layer is not within the scope of the present application, and the prepared lithium ion battery has a low first coulombic efficiency, cycle capacity retention rate and energy density.

[0194] It can be seen from Examples 1-1 and 2-1 to 2-4 that as the roller pressure P2 increases, the amount of lithium replenishment increases, the initial coulombic efficiency of the lithium-ion battery increases, the energy density increases, and the cycle capacity increases first and then decreases, indicating that excessive lithium replenishment will affect the cycle performance of the lithium-ion battery to a certain extent.

[0195] The type of interface particles usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 2-12 and 2-13 that the type of interface particles is within the scope of this application, and the prepared lithium-ion batteries have higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that it is possible to improve the initial coulombic efficiency of lithium-ion batteries, reduce cycle capacity attenuation, and improve the energy density of lithium-ion batteries. In Example 2-12, when the type of interface particles is single-walled carbon nanotubes, the thickness of the interface layer is affected by the diameter of the single-walled carbon nanotubes, and the thickness of the interface layer is relatively thin. After lithium supplementation, more by-products remain in the negative electrode material layer, affecting the initial coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery.

[0196] The type of lithium replenishment layer usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1 and 2-14 that the type of lithium replenishment layer is within the scope of this application, and the prepared lithium-ion battery has a higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that the initial coulombic efficiency of lithium-ion batteries can be improved, the cycle capacity attenuation can be reduced, and the energy density of lithium-ion batteries can be improved.

[0197] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0198] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0199] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for preparing a lithium supplement composite layer, comprising the following steps: (1) coating a lithium metal powder slurry on a support layer, drying it, and rolling it to form a lithium supplement layer; or rolling a lithium foil and / or a lithium alloy foil onto a support layer to form a lithium supplement layer; or coating a lithium or lithium alloy molten slurry on a support layer, cooling it, and rolling it to form a lithium supplement layer; wherein the rolling pressure P1 is 0.1T / 10mm to 2T / 10mm; (2) coating the interface particles on the surface of the lithium replenishing layer to form an interface layer, and then rolling the layer, wherein the rolling pressure P2 is 0.1T / 10mm to 2T / 10mm, the rolling temperature T1 is 25°C to 170°C, and the rolling standing time t1 is 5min to 50min, to form a lithium replenishing composite layer.

2. The preparation method according to claim 1, wherein The lithium supplement composite layer comprises the support layer, the lithium supplement layer and the interface layer, the lithium supplement layer is arranged between the support layer and the interface layer, the interface layer comprises the interface particles, and the lithium supplement layer comprises at least one of lithium foil or lithium alloy foil.

3. The preparation method according to claim 1, wherein The interface particles include at least one of a conductive agent or a lithium-intercalated material; the conductive agent includes at least one of conductive carbon black, carbon fiber, graphene or carbon nanotubes; the lithium-intercalated material includes at least one of artificial graphite, natural graphite, hard carbon, silicon-carbon material or silicon-oxygen material.

4. A lithium supplementation method comprising the following steps: Drying a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; The lithium-replenishing composite layer prepared by the preparation method described in any one of claims 1 to 3 and the negative electrode plate are laminated so that the interface layer is in contact with the negative electrode material layer, and a pre-lithiation treatment is performed, wherein the interface pressure P3 between the interface layer and the negative electrode material layer is 0.1 MPa to 2 MPa, the lamination time t2 between the interface layer and the negative electrode material layer is 0.5 h to 72 h, and the lamination temperature T2 between the interface layer and the negative electrode material layer is 50° C. to 180° C. After the pre-lithiation treatment is completed, the lithium-replenishing composite layer and the negative electrode plate are peeled off to form a pre-lithiation negative electrode plate.

5. A pre-lithiated negative electrode sheet prepared by the lithium replenishment method according to claim 4, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer, and along the thickness direction of the negative electrode sheet, the negative electrode material layer comprises a first surface and a second surface opposite to each other; From the first surface to the second surface, the negative electrode material layer includes a first region, a second region and a third region in sequence, and the third region is located on the surface of the negative electrode current collector; The thickness of the first region accounts for 1 / 3 of the thickness of the negative electrode material layer, the thickness of the second region accounts for 1 / 3 of the thickness of the negative electrode material layer, and the thickness of the third region accounts for 1 / 3 of the thickness of the negative electrode material layer; Based on the mass of the first region, the mass percentage of lithium element is W1, based on the mass of the second region, the mass percentage of lithium element is W2, based on the mass of the third region, the mass percentage of lithium element is W3, W1>W2>W3, 1.01≤W1 / W2≤2.0, 1.01≤W2 / W3≤2.

0.

6. The pre-lithiated negative electrode sheet according to claim 5, wherein: The negative electrode material layer includes a negative electrode active material, the negative electrode active material includes at least one of a carbon material or a silicon-containing material, the carbon material includes at least one of a graphite material or hard carbon, and the silicon-containing material includes at least one of a silicon-carbon material or a silicon-oxygen material.

7. The pre-lithiated negative electrode sheet according to claim 6, wherein: The negative electrode plate satisfies one of the following characteristics: (1) The negative electrode active material only includes the silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 18.6%≤w1≤63.5%, 11.5%≤W1≤18.4%, 9.2%≤W2<11.5%, 4.6%≤W3<9.2%; (2) The negative electrode active material includes the carbon material and the silicon-containing material. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 1.1%≤w1≤3.4%, 0.38%≤W1≤0.60%, 0.30%≤W2<0.38%, 0.15%≤W3<0.30%; (3) The negative electrode active material includes the carbon material and the silicon-containing material. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 3.3%≤w1≤10.2%, 2.8%≤W1≤4.5%, 2.2%≤W2<2.8%, 1.1%≤W3<2.2%.

8. The pre-lithiated negative electrode sheet according to claim 6, wherein: The porosity of the first region is S1, the porosity of the second region is S2, and the porosity of the third region is S3, where S1>S2>S3.

9. The pre-lithiated negative electrode sheet according to claim 8, wherein: 1.01≤S1 / S2≤1.5, 1.01≤S2 / S3≤1.

5.

10. The pre-lithiated negative electrode sheet according to claim 8, wherein: The negative electrode plate satisfies one of the following characteristics: (1) The negative electrode active material only includes the silicon-containing material. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 18.6%≤w1≤63.5%, 42.1%≤S1≤57.0%, 38.0%≤S2<42.1%, 25.0%≤S3<38.0%; (2) The negative electrode active material includes the carbon material and the silicon-containing material. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 1.1%≤w1≤3.4%, 26.3%≤S1≤35.5%, 23.7%≤S2<26.3%, 15.8%≤S3<23.7%; (3) The negative electrode active material includes the carbon material and the silicon-containing substance. Based on the mass of the negative electrode material layer, the mass percentage of silicon element in the negative electrode material layer is w1, 3.3%≤w1≤10.2%, 31.6%≤S1≤42.6%, 28.4%≤S2<31.6%, 18.9%≤S3<28.4%. 11 . A secondary battery comprising the pre-lithiated negative electrode sheet according to any one of claims 5 to 10. 12 . An electronic device comprising the secondary battery according to claim 11 .

Citation Information

Patent Citations

  • Lithium ion battery negative electrode single-side pre-lithiation method using three-dimensional foil

    CN108550780A

  • Positive plate, preparation method of positive plate, lithium ion battery and preparation method of lithium ion battery

    CN116435459A

  • Preparation method of interface layer pre-lithiation dry method negative electrode of lithium-containing multi-element alloy

    CN119050277A